Learning Module for Counseling - Koirala, Surya (Journal of Nursing Education of Nepal, 2023)
This article provides a training module that emphasizes specific counseling behaviors to facilitate a client-centered focus and to enhance the emotional–affective clinical environment. This learning module would influence counselors’ decisions to provide information confidently. The module will help individuals to become self-sufficient, self-dependent, self-directed and to adjust themselves efficiently to the day to day challenges in life.